Analytical investigation on the load-moment interaction behavior of the FRP reinforced geopolymer concrete filled FRP tube circular columns. (October 2021) - Ahmad, Junaid; Ali, Shehroze; Yu, Tao; Sheikh, M. Neaz; Hadi, Muhammad N.S.
Abstract: In this study, the load moment ( P - M ) interaction behavior of geopolymer concrete (GPC) filled fiber reinforced polymer (FRP) tube circular columns internally reinforced with FRP bars was analytically investigated. An analytical model for the P-M interaction behavior of the column was developed and validated against the experimental investigation results. The analytical model incorporates the confined GPC strength and the contribution of FRP bars in the load and moment capacities. In addition, a parametric study was conducted to investigate the influence of the compressive strength of the GPC, longitudinal reinforcement ratio and confinement ratio on the P - M interaction behavior of the column. The developed analytical model conservatively predicted the P - M interaction behavior of the column. It was found that the compressive strength of the GPC, the longitudinal reinforcement ratio and the confinement ratio significantly influenced the P - M interaction behavior of the column. All the tested parameters resulted in the linear increase of load and moment capacities with the increase in the tested parameter. Highlights: FRP bar reinforced GPC filled FRP tube columns were analytically investigated. Analytical model for the P-M interaction behavior of the column was developed. Experimental results were used to validate the analytical predictions. A parametric study was also conducted.